Probing the active site tryptophan of Staphylococcus aureus thioredoxin with an analog. Issue 22 (17th November 2015) - Englert, Markus; Nakamura, Akiyoshi; Wang, Yane-Shih; Eiler, Daniel; Söll, Dieter; Guo, Li-Tao
Abstract: Genetically encoded non-canonical amino acids are powerful tools of protein research and engineering; in particular they allow substitution of individual chemical groups or atoms in a protein of interest. One such amino acid is the tryptophan (Trp) analog 3-benzothienyl-l -alanine (Bta) with an imino-to-sulfur substitution in the five-membered ring. Unlike Trp, Bta is not capable of forming a hydrogen bond, but preserves other properties of a Trp residue. Here we present a pyrrolysyl-tRNA synthetase-derived, engineered enzyme BtaRS that enables efficient and site-specific Bta incorporation into proteins of interest in vivo . Furthermore, we report a 2.1 Å-resolution crystal structure of a BtaRSBta complex to show how BtaRS discriminates Bta from canonical amino acids, including Trp. To show utility in protein mutagenesis, we used BtaRS to introduce Bta to replace the Trp28 residue in the active site of Staphylococcus aureus thioredoxin. This experiment showed that not the hydrogen bond between residues Trp28 and Asp58, but the bulky aromatic side chain of Trp28 is important for active site maintenance. Collectively, our study provides a new and robust tool for checking the function of Trp in proteins.